Numerical modelling of the rise of Taylor bubbles through a change in pipe diameter - Ambrose, Stephen; Lowndes, Ian S.; Hargreaves, David; Azzopardi, Barry (Elsevier, 2017)
The rise of Taylor bubbles through expansions in vertical pipes is modelled using Computational Fluid Dynamics. The predictions from the models are compared against existing experimental work and show good agreement, both quantitatively and qualitatively. Many workers, including the present work, find that, as the bubble passes through the expansion, it will either remain intact or split into one or more daughter bubbles. We find that the critical length of bubble, defined as the maximum length that will pass through intact, is proportional to the cosecant of the angle of the expansion. Further, we show that for an abrupt expansion, the critical bubble length became unaffected by the walls of the upper pipe as the diameter was increased.